Enhanced efficiency of nonviral direct neuronal reprogramming on topographical patterns. (15th June 2021) - Mattiassi, Sabrina; Rizwan, Muhammad; Grigsby, Christopher L.; Zaw, Aung Moe; Leong, Kam W.; Yim, Evelyn K. F.
Abstract : Using high-throughput screening, we were able to identify topographies that can significantly improve the efficiency of nonviral neuronal reprogramming. Abstract : Nonviral direct neuronal reprogramming holds significant potential in the fields of tissue engineering and regenerative medicine. However, the issue of low reprogramming efficiency poses a major barrier to its application. We propose that topographical cues, which have been applied successfully to enhance lineage-directed differentiation and multipotent stem cell transdifferentiation, could improve nonviral direct neuronal reprogramming efficiency. To investigate, we used a polymer-BAM ( Brn2, Ascl1, Myt1l ) factor transfection polypex to reprogram primary mouse embryonic fibroblasts. Using a multiarchitecture chip, we screened for patterns that may improve transfection and/or subsequent induced neuron reprogramming efficiency. Selected patterns were then investigated further by analyzing β-tubulin III (TUJ1) and microtubule-associated protein 2 (MAP2) protein expression, cell morphology and electrophysiological function of induced neurons. Certain hierarchical topographies, with nanopatterns imprinted on micropatterns, significantly improved the percentage of TUJ1+ and MAP2+ cells. It is postulated that the microscale base pattern enhances initial BAM expression while the nanoscale sub-pattern promotes subsequent maturation. This is because the base pattern alone increased expression of TUJ1 and MAP2, while the nanoscale pattern was the only pattern yielding induced neurons capable of firing multiple action potentials. Nanoscale patterns also produced the highest fraction of cells showing spontaneous synaptic activity. Overall, reprogramming efficiency with one dose of polyplex on hierarchical patterns was comparable to that of five doses without topography. Thus, topography can enhance nonviral direct reprogramming of fibroblasts into induced neurons.